The Attempt At Stating The Influence Of Mother’s Age On The Development Of The Somatic Traits Of A Fetus - Cieślik, Krystyna; Waszak, Małgorzata (Anthropological Review, 1992)
The attempt at stating the influence of mother’s age on the development of the somatic traits of a fetus was made on the material composed of 1800 fetuses in the age of 20-40 weeks. By means of the variance analysis the correlation between 7 somatic traits o f a fetus and the age of a mother, was examined.